Mandibular defect reconstruction using three-dimensional polycaprolactone scaffold in combination with platelet-rich plasma and recombinant human bone morphogenetic protein-2: De novo synthesis of bone in a single case - Schuckert, K.-H. (2014)
10.1089/ten.tea.2008.0033